Primary care considerations for the pediatric endurance athlete - Watkins R. A.; Guillen, R: V. (Current Reviews in Musculoskeletal Medicine, 2024)
Purpose of Review This study aimed to provide an overview of some of the medical concerns surrounding the care of the pediatric endurance athletes and add to the limited literature specific to the pediatric endurance athlete.